PENGARUH FASILITAS BELAJAR DAN MOTIVASI BELAJAR TERHADAP PRESTASI BELAJAR MATA PELAJARAN EKONOMI SISWA KELAS XII IS DI SMA NEGERI 5 SURAKARTA TAHUN AJARAN 2015/2016 - Cynthia, Lela Camellia; Martono, Trisno; Indriayu, MIntasih (BISE: Jurnal Pendidikan Bisnis dan Ekonomi, 2015)
The objective of research were to find out the effect of learning facilities and learning motivation simultaneously towards economic lesson achievement in XI grade Social Sciences in SMA Negeri 5 Surakarta academic year 2015/2016. The method used in this study was descriptive quantitative method with survey. The sample in this study were 56 students’ XI grade Social Sciences in SMA Negeri 5 Surakarta academic year 2015/2016. The data collection techniques used questionnaires. The data were analyzed by using multiple regression analysis. The results showed that there was a significant positive effect of learning facilities and learning  motivation simultaneously towards economic lessonachievement. The magnitude of the effect of learning facilities and learning motivation towards economic lesson achievement simultaneously obtained from the calculation of the R- square of 47,9%.